2007
DOI: 10.1590/s1679-62252007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors predicting fish community structure in two neotropical rivers in Brazil

Abstract: In order to assess the organization patterns of the fish communities in the Jogui and Iguatemi rivers, we collected fish with gill nets tri-monthly from November 1999 to August 2000. Hypostomus ancistroides and Parauchenipterus galeatus were the most abundant species in the Jogui and Iguatemi rivers, respectively. Longitudinal variation was more important than seasonal in determining the species composition in both rivers, and the difference between seasons was not statistically significant. Altitude was the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
2
15
1
2
Order By: Relevance
“…This was early highlighted for steeped temperate rivers in North America (Burton & Odum, 1945), Europe (Huet, 1949) and South America (Petry & Schulz, 2006). This pattern was also revealed in tropical fluvial ecosystems where altitudinal gradient seems to be one of the most important factors determining fish species distribution (Hoeinghaus et al, 2004;Súarez & Petrere Júnior, 2007). Under such conditions, in spite of the higher number of species at lower reaches, some fish species occur exclusively at headwaters whereas others occur exclusively at downstream.…”
Section: Historical Records and Regional Biogeography Of Speciesmentioning
confidence: 77%
“…This was early highlighted for steeped temperate rivers in North America (Burton & Odum, 1945), Europe (Huet, 1949) and South America (Petry & Schulz, 2006). This pattern was also revealed in tropical fluvial ecosystems where altitudinal gradient seems to be one of the most important factors determining fish species distribution (Hoeinghaus et al, 2004;Súarez & Petrere Júnior, 2007). Under such conditions, in spite of the higher number of species at lower reaches, some fish species occur exclusively at headwaters whereas others occur exclusively at downstream.…”
Section: Historical Records and Regional Biogeography Of Speciesmentioning
confidence: 77%
“…Conductivity can be considered to be an indirect measure of the productivity of the system, i.e., environments with a higher conductivity tend to have a larger pool of dissolved nutrients and therefore a higher productivity (Swanson et al 2006), which can support more species. The response to conductivity seen in the cichlid assemblage of the Pantanal lagoons has also been demonstrated in communities of freshwater fish in temporary environments (Pazin et al 2006) and in large tropical rivers (Súarez and Petrere-Junior 2007).…”
Section: Effect Of Variations In Aquatic Habitat Conditions On Cichlimentioning
confidence: 80%
“…Araújo & Tejerina-Garro (2009), found that pH, water velocity, channel width and water temperature strongly affected fish assemblages in upper Paraná tributaries. Using geomorphologic data, Súarez & Petrere-Júnior (2007) suggested altitude as the most important structuring factor to fish community in the Iguatemi River basin. Apart from altitude, the water volume drained to a specific point seems to exert a large influence on the fish distribution patterns (Garutti, 1988).…”
Section: Methodsmentioning
confidence: 99%